PRADIGMATIC ANALYSIS OF SPEECH VERBS IN ENGLISH AND UZBEK LANGUAGE (SCIENCE TIME JOURNAL, 2023)
This study presents a pragmatic analysis of speech verbs in English and Uzbek, aiming to explore their usage patterns, discourse functions, and cultural implications. Drawing on a corpus-based approach, the study examines the speech act types performed by speech verbs, such as assertions, requests, questions, and directives, and investigates the pragmatic features exhibited by these verbs in each language. The analysis reveals both similarities and differences in the usage of speech verbs, highlighting the influence of cultural values on verbal communication. The findings contribute to our understanding of pragmatics and cross-cultural communication, providing insights for language teaching and intercultural interactions.